Quadriceps Strength Deficits After a Femoral Nerve Block Versus Adductor Canal Block for Anterior Cruciate Ligament Reconstruction: A Prospective, Single-Blinded, Randomized Trial. Issue 9 (25th September 2018) - Runner, Robert P.; Boden, Stephanie A.; Godfrey, William S.; Premkumar, Ajay; Samady, Heather; Gottschalk, Michael B.; Xerogeanes, John W.
Background: Peripheral nerve blocks, particularly femoral nerve blocks (FNBs), are commonly performed for anterior cruciate ligament (ACL) reconstruction. However, associated quadriceps muscle weakness after FNBs is well described and may occur for up to 6 months postoperatively. The adductor canal block (ACB) has emerged as a viable alternative to the FNB, theoretically causing less quadriceps weakness during the immediate postoperative period, as it bypasses the majority of the motor fibers of the femoral nerve that branch off proximal to the adductor canal. Purpose/Hypothesis: This study sought to identify if a difference in quadriceps strength exists after an ACB or FNB for ACL reconstruction beyond the immediate postoperative period. Beyond the immediate postoperative period, we anticipated no difference in quadriceps strength between patients who received ACBs or FNBs for ACL reconstruction. Study Design: Randomized controlled trial; Level of evidence, 1. Methods: A total of 102 patients undergoing primary ACL reconstruction using a variety of graft types were enrolled between November 2015 and April 2016. All patients were randomized to receive an ACB or FNB before surgery, and the surgeon was blinded to the block type. All patients underwent aggressive rehabilitation without functional bracing postoperatively. The time to the first straight-leg raise was reported by the patient. Isokinetic strength testing was performed at 3 and 6 months postoperatively. Results: Data for 73 patients were analyzed. There was no significant difference in patient demographics of age, body mass index, sex, or tourniquet time between the FNB (n = 35) and ACB (n = 38) groups. The mean time to the first straight-leg raise was similar, at 13.1 ± 1.0 hours for the FNB group and 15.5 ± 1.2 hours for the ACB group ( P = .134). The mean extension torque at 60 deg/s increased significantly for both the ACB (53.7% ± 3.4% to 68.3% ± 2.9%; P = .008) and the FNB (53.3% ± 3.3% to 68.5% ± 4.1%; P = .006) groups from 3 to 6 months postoperatively. There was also no significant difference in mean extension torque at 60 deg/s or 180 deg/s between the FNB and ACB groups at 3 and 6 months. There were no significant differences in postoperative complications (infection, arthrofibrosis, retear) between groups. Conclusion: Although prior studies have shown immediate postoperative benefits of ACBs compared with FNBs, with a faster return of quadriceps strength, in the current study there was no statistically or clinically significant difference in quadriceps strength at 3 and 6 months postoperatively in patients who received ACBs or FNBs for ACL reconstruction.